Enhancing anaerobic digestion of cotton stalk by pretreatment with a microbial consortium (MC1). (May 2016) - Yuan, Xufeng; Ma, Lei; Wen, Boting; Zhou, Dayun; Kuang, Meng; Yang, Weihua; Cui, Zongjun
Highlights: Effect of microbial pretreatment on methane yield of cotton stalk was evaluated. Soluble substrates in hydrolysate increased obviously after microbial pretreatment. CH4 production yields and rates significantly increased after microbial pretreatment. Abstract: Microbial pretreatment is beneficial in some anaerobic digestion systems, but the consortia used to date have not been able to effectively increase methane production from cotton stalk. In this study, a thermophilic microbial consortium (MC1) was used for pretreatment in order to enhance biogas and methane production yields. The results indicated that the concentrations of soluble chemical oxygen demand and volatile organic products increased significantly in the early stages of pretreatment. Ethanol, acetic acid, propionic acid, and butyric acid were the predominant volatile organic products in the MC1 hydrolysate. Biogas and methane production yields from cotton stalk were significantly increased following MC1 pretreatment. In addition, the methane production rate from the treated cotton stalk was greater than that from the untreated sample.